Studies on the Synthesis Process of Plant-Derived Ursodeoxycholic Acid Intermediates - Shaoxiong Jing; Zhongyue Wang; Yuan Wang; Yingquan Yang; Jian Song; Bao Zhang (Molecules)
Ursodeoxycholic acid (UDCA), a critical secondary bile acid in human physiology, demonstrates significant industrial potential through synthetic routes from bisnoralcohol (BA). Current synthetic routes rely on hydroxyl oxidation and Horner–Wadsworth–Emmons reactions as critical initial steps, facing unresolved challenges in reaction scale-up dynamics and impurity evolution. In this work, we systematically investigated the scale-up effects and innovatively addressed the impurity control problem. In the OH-C(22) selective oxidation of BA, the impurity C(22) carboxylic acid was synthesized, the emulsification was eliminated by process optimization, and the yield was increased from 89.0% to 95.2%. In the Horner–Wadsworth–Emmons reaction, the C(20)-methyl racemate and the C(22)-Z-ene isomer were synthesized, followed by the validation of the remaining byproducts. Based on impurity profile analysis, we innovatively modified the reaction feeding protocol, increased the yield from 79.1% to 90.8%, and significantly improved reaction selectivity. This optimized process demonstrates superior scalability and provides valuable insights for the industrial production of plant-derived UDCA.